Bridging the World Through Higher Education - Safei, Su'aidi (2013)
Education Malaysia Egypt (EME) is responsible to promote edu-tourism, to invite international students to study at universities in Malaysia. This encourages students’ mobility of other nations to choose as the study destination. Malaysia is already home to over 70 thousand students from 150 countries, a testimony that it is a centre of quality higher education.